2021
DOI: 10.3390/foods10092037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nutritional Knowledge, Attitudes and Practices between Urban and Rural Secondary School Students: A Cross-Sectional Study in Sabah, East Malaysia

Abstract: Nutritional knowledge, attitudes and practice (KAP) may guide healthy meal choices. Here, nutritional KAP was compared across school students in Sabah based on locality and gender. A cross-sectional survey of students aged 15–19 years was conducted using multistage sampling. Nutritional KAP was measured via questionnaire. Anthropometric measures of weight and height were taken in person to calculate body mass index (BMI). Among the 994 participants, 80% were urban and 60% were female (mean age 16.5 ± 0.6 yr). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
1
2
Order By: Relevance
“…This finding contradicted the evidence from previous studies, which showed no significant relationship between urbanization and nutrition knowledge (Steyn et al. , 2000; Jeinie et al. , 2021).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding contradicted the evidence from previous studies, which showed no significant relationship between urbanization and nutrition knowledge (Steyn et al. , 2000; Jeinie et al. , 2021).…”
Section: Discussioncontrasting
confidence: 99%
“…As compared to individuals in highurbanization states, those in low-urbanization states were less likely to have knowledge of the definition of calories, whereas those in middle-urbanization states were more likely to have knowledge of the effect of calories on body weight. This finding contradicted the evidence from previous studies, which showed no significant relationship between urbanization and nutrition knowledge (Steyn et al, 2000;Jeinie et al, 2021). It can be concluded that while health information is widely available in urban areas, residents in high-urbanization states may not always have good caloric knowledge.…”
Section: Calories and Its Influencing Factorscontrasting
confidence: 79%
See 1 more Smart Citation
“…The KAP theoretical model is frequently utilized in investigations and studies concerning diet behavior changes and public health issues [ 32 ]. Based on the fundamental principles of KAP theory, enhancing knowledge can bring about changes in attitudes and behaviors, consequently alleviating the burden of diseases [ 33 , 34 ]. Previous research has extensively examined the correlation between diet and health status among older adults [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study found no link between the history of nutrition education on breastfeeding and complementary feeding and the nutritional status of children in the Sumbang District. Nutrition education, on the other hand, is critical for boosting mothers' knowledge and awareness of feeding methods (36)(37). Inconsistent results could be attributed to a lack of data on nutrition education quality and delivery.…”
Section: Discussionmentioning
confidence: 99%